Reading Herodotus : A Guided Tour through the Wild Boars, Dancing Suitors, and Crazy Tyrants of The History - Hamel, Debra (Book collections on Project MUSE., 2012)
Debra Hamel's book is a lively introduction to The History of the Persian Wars, Herodotus' account of Persia's expansion under four kings - Cyrus, Cambyses, Darius, and Xerxes - and its eventual collision with the city-states of Greece. The History can be a long slog for modern readers, but is is full of salacious tales about sex, violent death, divine prophecies, and cannibals. Following the structure o f the original work, Hamle leads the reader through a colorful tour of the the central stories that compose The History. -- cover p. 4.